Investment Spillover Impact of The Jakarta Mass Rapid Transit Project: An Inter-Regional Input Output Analysis - Nurhidayati Nurhidayati; Lestari Kurniawati; Joko Sumantri; Rd. Yen Yen Nuryeni; Khoirul Huda (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study analyzes the economic spillover effects of investment in the Jakarta Mass Rapid Transit (MRT) project using an Inter-Regional Input Output (IRIO) approach. The analysis integrates realized investment from Phase I and projected investment from Phase II to capture both ex-post and ex-ante economic impacts across sectors and regions. Research Methodology: Using Indonesia’s IRIO table with 34 provinces and 17 sectors, this study estimates the multiplier effects on output, value added, and employment, while explicitly accounting for interregional leakages and production linkages. Results: The results indicate that MRT investment generates substantial economic impacts that are highly concentrated in DKI Jakarta. Interregional spillover effects to other provinces are present but relatively limited, reflecting Jakarta’s dominant intra-regional supply chains and strong agglomeration economies. The employment impact analysis shows that MRT investment creates jobs with the largest employment gains occurring in business services, construction, and wholesale–retail trade sectors. Conclusions: These findings confirm that urban rail infrastructure functions as a highly localized growth catalyst, strengthening metropolitan economic structures rather than evenly distributing benefits across regions. Limitations: The investment data used in this study only comes from grant and loan data from the Japan International Cooperation Agency (JICA) managed by Investment Treasury Office. Contributions: The study contributes to the literature by applying an IRIO framework to a large-scale urban transport project in Indonesia, providing empirical evidence on the magnitude and spatial distribution of infrastructure spillovers.